10.1159/000503210 (Inactive DOIs, 2000)
INTRODUCTION: Most studies of family communication about inherited risk of hereditary breast and ovarian cancer syndrome are conducted in high-risk clinic settings and show that cancer patients are highly selective in sharing inherited risk information. The reasoning processes behind this are not well understood and yet to be explored in population-based samples. METHODS: We conducted a secondary analysis of ovarian cancer survivors participating in the Your Family Connects communication intervention. Website use data were analyzed to assess survivors' choices of at-risk relatives for contact (i.e., total number and relationship). Retrospective online think-aloud interviews explored the decision-making processes driving which relatives were included or excluded. RESULTS: The 116 participants enumerated 164 relatives (mean = 1.41; mode = 0; range = 0 to 7). Approximately one-third of them (45/116, 38.8%) did not enumerate any relatives. Most of the participants who identified relatives (71/116) identified female relatives (95 women vs. 30 men in first-degree relatives; 29 women and 10 men in second-degree relatives). When survivors were asked to deliberate about their enumeration behaviors, they described making heuristic-based judgments about which relatives would be most likely to follow through on genetic counseling. Survivors considered that female relatives would have the most to gain, but the relatives' age and the extent of emotional closeness were also important in the decision-making process. CONCLUSION: Future research is needed in population-based samples to understand these qualitative drivers and consider decision-aid strategies to help cancer patients consider options for communication that are sensitive to the multifactorial context of at-risk relatives' lives.